Dual‐wideband bandstop filter using transversal signal‐interaction concept. Issue 9 (1st April 2013) - Xue, S.J.; Zhu, H.T.; Feng, W.J.; Che, W.Q.
Abstract : A dual‐wideband bandstop filter with high selectivity using transversal signal‐interaction concept is proposed. Five transmission poles in the passband between the two stopbands can be achieved due to the superposition of signals for the two transmission paths. A planar dual‐wideband bandstop filter prototype for WLAN bands with 10 dB fractional bandwidths of 76.2% and 26.9% has been designed and fabricated.